Minimization of embodied carbon footprint from housing sector of Malaysia - Gardezi, S.S.S. (Italian Association of Chemical Engineering - AIDIC, 2015)
The reduction in embodied carbon footprint is one of the major concerns in the construction industry. Among many other adopted techniques, the use of recycled materials is one of recommended method to lower the environmental effects of construction materials. However, the potential of recycled materials to offset the embodied carbon footprint from conventional Malaysian housing construction requires to be evaluated. The main focus of study was to perform a comparative analysis for minimization of embodied carbon footprint from the conventional materials used Malaysian housing industry by using recycled materials. A typical double story semi-detached house commonly constructed in Malaysian tropical climate was selected as case study. The model of the house was generated in a virtual environment using Building information modelling (BIM) process. The results highlighted that with incorporation of recycled materials within a range of 0 to 100 , the embodied carbon footprint offset potential varied up to 18 as compared to conventional construction. Copyright Â© 2015, AIDIC Servizi S.r.l.,.